Economic geology of the platinum metals - Mertie, John Beaver, 1888-1980 (Geological Survey professional paper, 1969)
A summary report on the geology of the platinum deposits of the world, with a discussion of the chemistry and mineralogy of the platinum group of metals and a comprehensive bibliography.